Domination or Stewardship?: The Old Testament and Ecology Between Lynn White and Desmond Tutu - Hwang, Jerry (Scriptura, 2025)
In a 1967 issue of Science, Lynn White claimed that "[e]specially in its Western form, Christianity is the most anthropocentric religion the world has ever seen… [and] not only established a dualism of man and nature but also insisted that it is God’s will that man exploit nature for his proper ends." White and many others have regarded such a subject-object relationship to nature as the teaching of the Old Testament itself, especially in its account of Adam being created in God’s image, ostensibly to bring nature into submission. This worldview of subjugating an unruly Other (both people and resources) would become the pseudo-biblical rationale for wars of conquest by Christendom’s empires. By contrast, Bishop Desmond Tutu is prominent among non-western thinkers who hold that the imago Dei in humanity stands opposed to every form of colonial domination of the Other. Tutu also extends his signature notion of Ubuntu (human interdependence) to include the entire created order within "Eco Ubuntu." Since the Old Testament has thus featured in both (more) western narratives of unfettered domination over nature as well as (more) non-western narratives of creation stewardship, it is essential to adjudicate between these religio-cultural clashes in interpretation during the Anthropocene by revisiting the witness of the Bible’s creation texts. In showing that holism characterises the most recent creation theologies, this study will also examine recent uses of the Old Testament in the rather disparate arguments of advocates of subsistence economics, sceptics of global warming, and climate apocalypticists.